Organic matter dynamics in the recovery of clearings of the Amazon forest, Brazil - Moreira, Adônis; Costa, Danielle Gonçalves (Pesquisa Agropecuaria Brasileira, 2004)
The removal of native forest as well as of the surface soil horizons causes a significant decrease of microbial biomass and soil fertility. A slow and continuous recovery of the amount and of the quality of organic matter occurs in these areas, with reforestation. The objective of this work was to evaluate the fertility, organic matter and microbial biomass dynamics in areas reforested at different ages. The reforested clearings were set up in 2003, 2002, 2001, 1999 and 1993, with native regional species. The soil fertility was associated to soil organic matter content. The reforestation increased significantly the organic matter and the microbial biomass after the fourth year, and this indicates the need of an initial soil supply of carbon content, which can be provided by grasses or legumes used for forage.